2015
DOI: 10.1038/srep10059
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the Numerosity ‘zero’ in the Parietal Cortex of the Monkey

Abstract: Zero is a fundamental concept in mathematics and modern science. Empty sets are considered a precursor of the concept of numerosity zero and a part of numerical continuum. How is numerosity zero (the absence of visual items) represented in the primate cortex? To address this question, we trained monkeys to perform numerical operations including numerosity zero. Here we show a group of neurons in the posterior parietal cortex of the monkey activated in response to numerosity ‘zero’. ‘Zero’ neurons are classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 29 publications
(34 reference statements)
5
29
0
Order By: Relevance
“…Nieder and Miller, 2003;Tudusciuc and Nieder, 2007). Overwhelming evidence indicates that the primate brain place codes numerosity (Andreas Okuyama et al, 2015) even in monkeys that were never trained to discriminate numbers (Viswanathan and Nieder, 2013). Converging evidence from human fMRI adaptation studies revealed that tuned number neurons respond to dot arrays (Jacob & Nieder, 2009;Piazza et al, 2004).…”
Section: The Three Parietal Circuits Modelmentioning
confidence: 99%
“…Nieder and Miller, 2003;Tudusciuc and Nieder, 2007). Overwhelming evidence indicates that the primate brain place codes numerosity (Andreas Okuyama et al, 2015) even in monkeys that were never trained to discriminate numbers (Viswanathan and Nieder, 2013). Converging evidence from human fMRI adaptation studies revealed that tuned number neurons respond to dot arrays (Jacob & Nieder, 2009;Piazza et al, 2004).…”
Section: The Three Parietal Circuits Modelmentioning
confidence: 99%
“…A fascinating new study by Okuyama, Kuki, and Mushiake (2015) specifically assessed the contributions of parietal lobe activation in monkeys for the concept of zero, and these results further demonstrated continuity in numerical cognition across species. The concept of zero exists even in human societies without formal number notation systems.…”
mentioning
confidence: 90%
“…Okuyama et al (2015) extended the behavioral assessment of zero to ask whether parietal contributions of the processing of empty sets fit the broader model of numerical representation in monkeys’ brains, or somehow looked qualitatively different. They did this by analyzing activity in the ventral intraparietal (VIP) cortex, an area previously shown to have numerosity-specific neurons in single-neuron recording studies with monkeys (e.g., Nieder & Miller, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a prior study indicated that primate VIP neurons encode zero numerosity, although the lack of in vivo single-cell recordings from the PFC[ 2 _ T D $ D I F F ] -[ 3 _ T D $ D I F F ] a key brain structure for the encoding of abstract quantity[ 4 _ T D $ D I F F ] -[ 5 _ T D $ D I F F ] prevented the authors from observing any possible dissociations within the parietofrontal number network [10]. This is what the study by RamirezCardenas and colleagues directly investigated [9].…”
mentioning
confidence: 99%